Patterns of work-related stress and their predictors among emergency department nurses and emergency medical services staff in a time of crisis: a latent profile analysis - Edyta Charzyńska; Aghil Habibi Soola; Naser Mozaffari; Alireza Mirzaei (BMC, 2023)
Abstract Background Previous studies have shown that a disease outbreak may cause high stress among healthcare workers. However, the vast majority of those studies applied a variable-centered approach, in which relationships between the variables are believed to be identical across the studied population. The main purpose of this study was to identify latent profiles of healthcare workers with similar combinations of levels of various work-related stressors during the coronavirus disease 2019 (COVID-19) pandemic and to examine their predictors. Methods A cross-sectional paper-and-pencil study was conducted among a convenience sample of 297 emergency department (ED) nurses and 219 emergency medical services (EMS) staff members working in 10 hospital EDs and 52 EMS centers in Ardabil province, Iran. Data were collected using the Health and Safety Executive Management Standards Indicator Tool (HSE-MS IT). Results Using the latent profile analysis (LPA), five work-related stress profiles were identified: "high stress with a good understanding of one's job role" (11.1%), "moderate stress" (41.9%), "relatively high stress with average demands and a very low understanding of one's job role" (23.8%), "low stress" (18.0%), and "generally low stress but with very high job demands and relational conflicts" (5.2%). Age, marital status, service location, workplace, and the number of overtime hours significantly predicted profile membership. Conclusion The results of the study suggest the importance of incorporating various sources of stress and using the person-centered approach when investigating the work-related stress of healthcare workers during disease outbreaks. Identifying sociodemographic and work-related predictors of profile membership may be useful for preparing interventions that will be better suited to healthcare workers' needs.